High temperature viscosity of calcium-magnesium-aluminosilicate glass from synthetic sand. (November 2016) - Wiesner, Valerie L.; Vempati, Udaya K.; Bansal, Narottam P.
Abstract: Viscosity of a calcium-magnesium-aluminosilicate (CMAS) glass, melted from a synthetic sand with composition replicating that of air-breathing turbine engine deposits, was experimentally measured between 1215 °C and 1520 °C using a rotating spindle viscometer. Chemical composition of the CMAS glass before and after viscosity measurements was nominally 23.3CaO-6.4MgO-3.1Al2 O3 -62.5SiO2 -4.1Na2 O-0.5K2 O-0.04Fe2 O3 (mol.%) as determined using inductively coupled plasma atomic emission spectroscopy. Experimental viscosity values were compared with those estimated from composition-based calculators of Giordano et al., Fluegel and FactSage software. Although none of these models exactly predicted viscosity values, those determined by Fluegel and FactSage models were found to more closely match experimental viscosity of the CMAS glass. Graphical abstract: